Different Processed Products of Curcumae Radix Regulate Pain-Related Substances in a Rat Model of Qi Stagnation and Blood Stasis - Chen, Zhimin; Hu, Lin; Liao, Yujiao; Zhang, Xi; Yang, Zhuo; Hu, Changjiang; Yu, Lingying (Frontiers in Pharmacology, 2020)
Background Curcumae blood Radix (Yujin) has been widely used to treat Qi stagnation and stasis in TCM. According to the Chinese Pharmacopoeia, the tuberous roots of Curcuma longed L. (i.e., Huangsiyujin, HSYJ) is one of the major species of Yujin. According to the processing theory of TCM, stir-frying HSYJ with vinegar might strengthen the effect of dispersing stagnated hepatoqi to relieve pain, and stir-frying HSYJ with wine might strengthen the effect of promoting blood circulation in order to remove blood stasis. However, the mechanism for the enhancement of clinical efficacy by processing is unclear. Aim/Hypothesis This study was aimed at evaluating the effect of different processed products of HSYJ on chemical constituents and pain-related substances to explore underlying mechanisms of HSYJ in treating pain caused by Qi stagnation and blood stasis. Methods The effects of different processing methods on the paste yield of water decoction were analyzed, and the content of the main constituents were detected by HPLC. A rat model of Qi stagnation and blood stasis was established by tail clamp stimulation combined with subcutaneous adrenaline injection. After treatment and intervention with HSYJ and its processed products, β-endorphin (β-EP) and 5-hydroxytryptamine (5-HT) were measured by ELISA, and the expression of c-fos was evaluated by immunohistochemistry. Results After stir-frying with vinegar or wine, the extract yield and curcumin content increased. Compared with model group, raw HSYJ could significantly improve the abnormality of 5-HT in plasma (P < 0.05) and β-EP in brain (P < 0.01). Stir-frying HSYJ with vinegar or wine could significantly improve the abnormality of 5-HT in plasma, β-EP in brain, and the expression of c-fos (P < 0.01). Stir-frying HSYJ with vinegar could also significantly increase the level of β-EP in plasma (P < 0.05). Conclusion These results showed that different processing methods have certain effects on the chemical constituents of HSYJ, mainly in increasing the decoction rate and curcumin content. HSYJ and its processed products can reduce 5-HT levels, increase β-EP levels, and inhibit the expression of c-fos in model rats. The effects of stir-frying HSYJ with vinegar on β-EP levels in plasma was superior to others.